Differences in trophic structure and trophic pathways between artificial reef and natural reef ecosystems along the coast of the North yellow Sea, China, based on stable isotope analyses - Rongliang Zhang (Elsevier, 2021)
Artificial reefs have been employed to promote enrichment of degraded habitats communities and support local fisheries. To better evaluate the performance of artificial reefs, simultaneous comparisons with relatively undisturbed natural reefs nearby are essential. With the inclusion of the stable isotope method to characterize and compare ecosystem functioning for two reef systems, both trophic structure and trophic flow at an artificial and at a nearby natural reef are evaluated in the present work. We found that: 1) both macrobenthos and fish can be clustered into five trophic groups for each site, with similar grouping configurations in trophic structures, and 2) energy pathways both from basal resources to macrobenthos and from macrobenthos are similar between the artificial reef and the natural reef, although the pathway magnitudes may be spatially different. To elucidate the trophic pathways from a comprehensive viewpoint, we reconstructed a general model from basal resources up to fishes at each site, where pelagic pathway based on POM and benthic pathway based on either Chlorophyta or a mixture of microphytobenthos, POM and Chlorophyta are identified. We conclude that an artificial reef ecosystem that has been established for years can support a trophic structure and trophic pathways similar to those provided by a natural reef ecosystem. In the future, we call for comparisons of specific trophic compartments and the combination of trophic ecology and community structure, to better understand the development of artificial reef systems.